Primary Retroperitoneal Approach to the Superior Mesenteric Vessels in Minimally Invasive Surgical Treatment of Right Colon Cancer with D3 Lymph Node Dissection. Technique and First Short-Term Outcomes - S. K. Efetov; B. S. Semchenko; A. K. Rychkova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to develop and describe the technique of primary retroperitoneal approach to the superior mesenteric vessels for D3 lymph node dissection in minimally invasive surgical treatment of the right colon cancer; to evaluate the shortterm results of the first series of patients operated by this technique.Materials and methods. Patients with adenocarcinoma of the right colon were included in the study. The technique of primary retroperitoneal approach consisted in mobilization of the right mesocolon along the posterior surface in the direction of the superior mesenteric vessels, D3 lymph node dissection with crossing of the feeding vessels from the retroperitoneal side using a single-port access system and consisted of five consecutive steps. At the last step of the procedure the peritoneum and the remaining part of the mesentery were crossed laparoscopically to the intended borders of the colon resection. The specimen was extracted through the incision for the single port, followed by the formation of an anastomosis extracorporeally. The endpoints of the study were the short-term results of surgical treatment.Results. The study presents data of the first 5 patients with adenocarcinoma of the right colon who underwent surgical treatment with D3 lymph node dissection using primary retroperitoneal approach to the superior mesenteric vessels. The duration of the retroperitoneal step averaged 110 (90–140) min. The average blood loss was 62 (10–100) mL. The first two patients underwent a three-stage retroperitoneal portion of the surgery. The other three patients were successfully operated by primary retroperitoneal approach with performing of all five steps of the operation. The number of removed regional lymph nodes was on average 36 (18–57), apical lymph nodes — 6 (4–5), metastatic regional lymph nodes — 3 (2–4). One patient developed a Class 1 Clavien — Dindo complication, which did not require a change in treatment tactics. The average postoperative hospital stay was 8 (5–12) days.Conclusion. The technique of primary retroperitoneal approach to the superior mesenteric vessels to perform D3 lymph node dissection was described for the first time. The obtained results demonstrated the possibility of using this method for minimally invasive radical treatment of right colon cancer.